Estilos de liderazgo en los directivos y el desempeño laboral de los servidores de la Municipalidad Provincial de Ucayali - Contamana 2023 - Rojas Perea, Carla Jannet (2025)
The objective is to examine how leadership styles impact the labor performance of public employees of the Provincial Municipality of Ucayali – Contamana 2023. This investigation includes a basic, explanatory and quantitative study, with a non-experimental, transversal and correlational design causal. The sample is made up of 106 public servants, obtained through a museum census. A form was used with 82 questions to evaluate leadership styles and 10 statements to evaluate work performance, with answers on an ordinal scale. The result is 38% of the population studied presents satisfactory work performance, 62% is somewhat satisfactory and 0% is unsatisfactory. Executives achieved 58% in transformational leadership style, 32% in transactional, and 10% in coercive leadership. The first dimension reflects a weak positive correlation between transformational leadership style and weak transactional leadership and work performance, the third dimension reflects a weak negative correlation between coercive leadership and work performance. It is concluded that there is a slight positive correlation between the style of managerial leadership and labor performance, observed in public servants of the Provincial Municipality of Ucayali - Contamana 2023.